Head Teachers’ Role in Facilitating School Facilities that Influence Pupils’ Performance in Kcpe - Mbunde, John M. (European Scientific Journal, ESJ, 2017)
This paper discusses the head teachers’ role in facilitating school facilities that influence pupils’ performance in Kenya Certificate of Primary School (KCPE). The objective was to establish the head teachers’ role in facilitating school facilities that influence pupils’ performance in Kenya Certificate of Primary School. The research was based on the Max Weber’s Theory of Bureaucracy. The target population was 612 head teachers, senior teachers and accounts’ clerks in Nairobi County. The sample size was 123. The research employed descriptive survey design. The schools selected were 14 from Westland and Dagoretti districts and 13 from Lang’ata district through simple random sampling. The head teachers and accounts’ clerks were selected by purposive sampling methods. The research instruments used were the interview and document analysis guides. Validation of both instruments was done by the expert judgment review by supervisors from the Department of Educational Administration and Planning of the University of Nairobi. Descriptive statistics was used to analyze the data which was presented in a table. The study established that all the 41 sampled schools had fairly adequate exercise books, buildings and furniture; inadequate textbooks, radios, equipment, computers, displays, charts and playgrounds. The study concluded that the head teachers had not facilitated adequate school facilities that influence pupils’ performance in Kenya Certificate of Primary School (KCPE). It was recommended that the Ministry of Education, Science and Technology should increase funding of schools to enable the head teachers to procure more school facilities to enhance pupils’ performance in Kenya Certificate of Primary School.